Perancangan Interior Museum Pers Indonesia Di Surabaya - Wellyanto, Diana Selvia (Intra, 2015)
One of the attractive media to attract people to the journalistic work of the nation is Museum Pers Indonesia. Meanwhile, in Surabaya, there is not a space or a special container that can accommodate and facilitate historical documentation written by journalists during the colonial era in Surabaya. Based on these problems, it will be designed a museum press storage Indonesian struggle informative, educational, and recreation for Surabaya people and create an atmosphere of museum storage space press the Indonesian struggle that tells the history of the press.This sceme raised the concept strait to the free want to create a design that tells a press trip in Indonesia which stems from unfettered and experiencing freedom. Basically want to create a storage space that can tell a press trip in Indonesia, with the lifting of vintage modern design style.